'You can't walk through water without getting wet' UK nurses' distress and psychological health needs during the Covid-19 pandemic: A longitudinal interview study. (July 2022) - Maben, J.; Conolly, A.; Abrams, R.; Rowland, E.; Harris, R.; Kelly, D.; Kent, B.; Couper, K.
Abstract: Background: Pre-COVID-19 research highlighted the nursing profession worldwide as being at high risk from symptoms of burnout, post-traumatic stress disorder (PTSD) and suicide. The World Health Organization declared a pandemic on 11th March 2020 due to the sustained risk of further global spread of COVID-19. The high healthcare burden associated with COVID-19 has increased nurses' trauma and workload, thereby exacerbating pressure on an already strained workforce and causing additional psychological distress for staff. Objectives: The Impact of COVID-19 on Nurses (ICON) interview study examined the impacts of the pandemic on frontline nursing staff's psychosocial and emotional wellbeing. Design: Longitudinal qualitative interview study. Settings: Nurses who had completed time 1 and 2 of the ICON survey were sampled to include a range of UK work settings including acute, primary and community care and care homes. Interviewees were purposively sampled for maximum variation to cover a broad range of personal and professional factors, and experiences during the COVID-19 pandemic, including redeployment. Methods: Nurses participated in qualitative in-depth narrative interviews after the first wave of COVID-19 in July 2020 ( n  = 27) and again at the beginning of the second wave in December 2020 ( n  = 25) via video and audio platform software. Rigorous qualitative narrative analysis was undertaken both cross-sectionally (within wave) and longitudinally (cross wave) to explore issues of consistency and change. Results: The terms moral distress, compassion fatigue, burnout and PTSD describe the emotional states reported by the majority of interviewees leading many to consider leaving the profession. Causes of this identified included care delivery challenges; insufficient staff and training; PPE challenges and frustrations. Four themes were identified: (1) 'Deathscapes' and impoverished care (2) Systemic challenges and self-preservation (3) Emotional exhaustion and (4) (Un)helpful support. Conclusions: Nurses have been deeply affected by what they have experienced and report being forever altered with the impacts of COVID-19 persisting and deeply felt. There is an urgent need to tackle stigma to create a psychologically safe working environment and for a national COVID-19 nursing workforce recovery strategy to help restore nurse's well-being and demonstrate a valuing of the nursing workforce and therefore support retention.